Answer:
see explanation
Explanation:
Given
2x² - 7x + 3 = 0
Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term
product = 2 × 3 = 6 and sum = - 7
The factors are - 6 and - 1
Use these factors to split the x- term
2x² - 6x - x + 3 = 0 ( factor the first/second and third/fourth terms )
2x(x - 3) - 1(x - 3) = 0 ← factor out (x - 3) from each term
(x - 3)(2x - 1) = 0
Equate each factor to zero and solve for x
x - 3 = 0 ⇒ x = 3
2x - 1 = 0 ⇒ 2x = 1 ⇒ x =
![(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ybjkeso7qr5r7js5h0mv9de35dih0sxfpl.png)